The Efforts to Improve Students Academic Achievement By Implementing Somatic Auditory Visualization Intellectually (SAVI) and Talking Stick Approach. - Jimmy Nganta Ginting; Iwan Henri Kusnadi; Ilham Arief; Yoseb Boari; Afrizal Afrizal (Departement of Mathematics Education, 2023)
This investigative method is quantitative and uses experimental techniques with a posttest-only control design. The research focus is on students as a population, with cluster random sampling used for selection. Class B was used as the experimental class, while Class C was used as the control group. Data is collected through documentation and testing. The results of data analysis using the SAVI (Somatic Auditory Visualization Intellectually) approach and the Talking Stick approach show an increase in the average learning outcomes in the experimental class. In contrast, the control class uses a conventional learning model using the lecture method. Data analysis used the t-test, and because t-count > t-table, H0 was rejected. This means that the average learning outcomes of Class B students using the SAVI (Somatic Auditory Visualization Intellectually) collaborative approach and the Talking Stick approach are the same or greater than the learning outcomes of Class C students using the conventional lecture method.